Sebaran Ukuran Cangkang Kerang Bakau (Polymesoda bengalensis) Di Muaro Nipah Kecamatan Sutera Kabupaten Pesisir Selatan - Putri, Mira Prima; Widiana, Rina; Nurdin, Jabang (Pendidikan Biologi, 2013)
ABSTRACTÂ Muaro is one of the water bodies in which a variety of living organisms, the organism is clam shells Polymesoda bengalensis is known by the public as the seashell. The shells used by people around for a living because of the economic and nutritional value is very high. Current where abouts shellfish habitat Polymesoda bengalensis already disturbed. The most serious threat to the population is the result of harvesting clams and mussels taking excessive. Organisms that live in Muaro depending on substrate conditions and salinity, the salinity fluctuations depending on topography estuaries and tidal influence, the substrate Â showed Â differences Â withÂ  population densities. This factor Â caused by Â each type of Â substrate occupied by Polymesoda bengalensis shells with different age groups. This study aimed to determine the distribution of oyster shell length and physical factors-water chemistry of mangrove clams Polymesoda bengalensis in Muaro Nipah Kecamatan Sutera Kabupaten Pesisir Selatan. The research was conducted in Â JanuaryÂ  2013 Â in Â Muaro Â Nipah Â Kecamatan Â Sutera Â Kabupaten Â Pesisir Â Selatan. Â Analyzes Â were Polymesoda bengalensis conducted in the laboratory Animal Ecology Department of Biology, Faculty of Mathematics Â and Â Natural Â Sciences,Â  AndalasÂ  University Â inÂ  Padang, Â this Â determination Â using Â survey methods and sampling techniques using purposive systematic stratified random sampling in three locations determined by vegetation. Results of sample analysis shells Polymesoda bengalensis obtained size comparison long: thick : high = 2 : 1 : 2, there is a close relationship between the length and height with thick shells Polymesoda bengalensis. Biomass of meat is determined by the length, thickness and height shells. Length ranged shells 2.9â7 cm. Shell size distribution in strata I and III predominantly young individuals, in strata II adult individuals while on location I and III predominantly young individuals and locations II dominated by adult individuals.Â